Election of Village Heads as a Framework for Democracy within the Framework of the Unitary State of the Republic of Indonesia - Rosita , Lita (JURNAL RUANG HUKUM, 2023)
This research aims to find out the meaning of democracy, as well as how the election of village heads is a framework for democracy within the framework of the Unitary State of the Republic of Indonesia. In this research, the literature study method was used. The results of the research showed that democracy in an election had begun with the election of village heads and continued with the election of members of the DPR, DPRD, DPD, the election of Governor/Regent/Mayor and the election of President and Vice President, all of which were carried out based on provisions of laws and regulations within the framework of the Unitary State of the Republic of Indonesia.